Synaptic plasticity through a naturalistic lens - Piette, Charlotte; Gervasi, Nicolas; Venance, Laurent (Frontiers in Synaptic Neuroscience, 2023)
From the myriad of studies on neuronal plasticity, investigating its underlying molecular mechanisms up to its behavioural relevance, a very complex landscape has emerged. Recent efforts have been achieved towards more naturalistic investigations as an attempt to better capture the synaptic plasticity underpinning of learning and memory, which has been fostered by the development of in vivo electrophysiological and imaging tools. In this review, we examine these naturalistic investigations, by devoting a first part on synaptic plasticity rules issued from naturalistic or in vivo-like activity patterns. We next give an overview of the novel tools, which enable an increased spatio-temporal specificity for detecting and manipulating plasticity expressed at individual spines up to neuronal circuit level during behaviour. Finally, we put particular emphasis on works considering brain-body communication loops, such as macroscale contributors to synaptic plasticity, body internal states and brain energy metabolism.